1996
DOI: 10.1029/95jd00411
|View full text |Cite
|
Sign up to set email alerts
|

Trace gas measurements and air mass classification from a ground station in Taiwan during the PEM‐West A experiment (1991)

Abstract: Measurements of the ambient concentrations of 03, NOx (NO + NO2), and PAN (peroxyacetyl nitrate) were collected at Kenting, a rural site near the southern end of Taiwan, during the autumn of 1991 as part of the Pacific Exploratory Mission -West A (PEM-West A) experiment. Two principal component analyses (PCAs) were performed on the data. The results of the PCA indicated that at least three different air mass types were observed at the site, including marine boundary layer, urban plume, and continental outflow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…This may reflect the fact the air mass from the central northern Pacific sometimes has to pass over the large emission source region of southern Taiwan Island and the eastern coast of south China as revealed by individual trajectory. The median ozone concentrations associated with maritime air masses from the central Pacific and the South China Sea measured at Cape D'Aguilar in summer (21 and 13 ppbv respectively) are comparable in magnitude to those observed at Oki, Okinawa of Japan (11–15 and 22 ppbv respectively) and Kenting of Taiwan (9 and 18 ppbv respectively) [ Akimoto et al , 1996; Buhr et al , 1996].…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…This may reflect the fact the air mass from the central northern Pacific sometimes has to pass over the large emission source region of southern Taiwan Island and the eastern coast of south China as revealed by individual trajectory. The median ozone concentrations associated with maritime air masses from the central Pacific and the South China Sea measured at Cape D'Aguilar in summer (21 and 13 ppbv respectively) are comparable in magnitude to those observed at Oki, Okinawa of Japan (11–15 and 22 ppbv respectively) and Kenting of Taiwan (9 and 18 ppbv respectively) [ Akimoto et al , 1996; Buhr et al , 1996].…”
Section: Resultsmentioning
confidence: 82%
“…Chan et al [1998aChan et al [ , 1998b proposed that the changes of prevalent maritime and continental air mass flow are important factors governing the variation of surface ozone in Hong Kong. Buhr et al [1996] and Wang et al…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The seasonal ΔO 3 /ΔNO y averages indicate an approximately 80‐fold, 100‐fold, and 60‐fold enrichment of O 3 relative to NO y (ppbv ppbv −1 ) during spring and fall, summer, and winter, respectively. The ΔO 3 /ΔNO y of 100 ppbv ppbv −1 is an order of magnitude higher than that observed in several rural sites in North America during the summer seasons (8.5–10 ppbv ppbv −1 [ Trainer et al , 1993; Olszyna et al , 1994]), is on the upper limit of what was encountered in the FT over North America (∼38–100 ppbv ppbv −1 [ Ridley et al , 1994]) and is moderately larger than those reported over the western North Atlantic region (∼10–50 ppbv ppbv −1 [ Buhr et al , 1996]). The summer ΔO 3 /ΔNO y observed at the Pico Mountain station is thus consistent with formation of O 3 over the continent and adjacent region, followed by a high NO y loss (via HNO 3 wet/dry deposition) and moderate O 3 destruction during transit to the measurement site.…”
Section: Impacts Of North American Anthropogenic Emissionsmentioning
confidence: 79%
“…These long‐term ambient air measurements taken in Taiwan can be used to document both chemical (e.g., chemical climatology) and transport characteristics (e.g., transport corridors) of the Asian continental outflows, including seasonal and interannual variability, long‐term trends, and the effect of climate change on long‐range transport [ CENR , 2001]. For example, Oltmans et al [2004] showed that long‐range transport of pollution from China in the spring affects boundary‐layer ozone concentrations at Taipei (25°N, 121.5°E); Taiwan has been one of the major sites in several Pacific field campaigns such as the Pacific Exploratory Missions [ Buhr et al , 1996; Arimoto et al , 1996; Akimoto et al , 1996; Liu et al , 1997; Arimoto et al , 1997; Board et al , 1999], ACE‐Asia [ Huebert et al , 2003], and TRACE‐P [ Jacob et al , 2003; Wild et al , 2004; Oltmans et al , 2004].…”
Section: Introductionmentioning
confidence: 99%